Forestry and shrub species associated to Maconellicoccus hirsutus (Green) (Hemiptera: Pseudococcidae) in northern Nayarit, Mexico - Isiordia-Aquino, Néstor; Robles-Bermudez, Agustín; García-Martínez, Oswaldo; Lomelí-Flores, Refugio; Flores-Canales, Ricardo; Gómez-Aguilar, J. Roberto; Espino-Alvarez, Rosalba (Instituto de Ecología, A.C., 2012)
The presence of pink hibiscus mealybug (PHM), Maconellicoccus hirsutus (Green) (Hemiptera: Pseudococcidae), causes environmental and socioeconomic damage in Nayarit, México. Thispest demands studies in order to help develop a management program that includes the knowledge of their hosts. The objectives of this study were to determine the hosts of this pest, such as trees or shrubs, and to know the levels of infestation on them. In 2009 there were selected and sampled 9235 points that included areas such as marginal, urban, agricultural, forestry and nurseries in seven municipalities of northern Nayarit. Also there 37 species were checked as possible host. The insect was present in 1070 points (11.6%), of them 94% presented an infestation at level one (low), to level two 5.6% (medium), and only 0.4% to level three (high). The most infested areas were the marginal (69.3%) and urban (24.9%); the municipalities with higher infestations were Tuxpan, Ruiz, and Rosamorada with an average of 35.2, 22.3, and 12.4%, respectively. About host plants there were recorded 24 species, included in nine botanical families, predominantly those belonging to the family Leguminosae; five of the identified plant species corresponded to new reports with PHM presence in the world. The most abundant and preferred to PHM were three leguminous species; however, the plant species that was present in all municipalities and predominant was Acacia cochliacantha Schlecht & Cham (30.9% infestation), followed by Mimosa pigra L. (19.3%) and Albizia lebbeck (L.) Benth (14.5%).